Rfid-технологии. развитие и области применения - Вышванюк, С. В. (ХНУРЕ, 2019)
This article is devoted to review of modern technologies for building RFID identification systems. The general characteristics of RFID systems and their comparison with other identification methods are given. The classification of tagging technologies and the features of active and passive RFID tags with a chip are shown. The areas of use of RFID technologies are considered